Journalists’ Perceptions of Press Release Quality at the Institut Teknologi Sumatera - Rudiyansyah; Tina Kartika; Andy Corry Wardhani (IJESS International Journal of Education and Social Science, 2026)
This study aims to explore how journalists interpret the quality of press releases produced by the Public Relations Office of the Sumatera Institute of Technology (Itera), particularly in relation to news values and the practical needs of journalistic work. The research employs a descriptive qualitative method by collecting data through in-depth interviews with six journalists from local and national media who routinely receive and process Itera’s press releases into news articles. The findings indicate that journalists view Itera’s press releases as having met basic technical standards, including the completeness of the 5W+1H elements, the use of the inverted pyramid structure, and adherence to standard Indonesian language conventions. However, journalists also identified several areas needing improvement, particularly the simplification of scientific terminology, deeper elaboration of research and technological innovations, and broader angles so that releases are not solely focused on ceremonial events. Additionally, journalists emphasized the need for an increased number of releases, better access to expert sources, and a more narrative and publicly relevant writing style. This study highlights that the effectiveness of a press release is not solely determined by the completeness of its data but also by the ability of public relations practitioners to produce messages that carry strong news value, making them more engaging and beneficial for both journalists and the public. Therefore, the study recommends strengthening science communication skills, increasing the volume of press releases, and adjusting writing styles to better meet media needs.